219 The effectiveness of onsite ACL injury prevention education for young athletes. (3rd March 2020) - Janosky, Joseph; Ologhobo, Titilayo; Russomano, James; Goldsmith, Sandra; Robbins, Laura
Abstract : Background: ACL injury prevention programs have demonstrated high levels of efficacy in controlled clinical trials, but the preventive interventions utilized in these programs do not typically include educational components rooted in behavior change theory, especially for youth and adolescent athletes. Objective: The purpose of this study is to evaluate the effectiveness of onsite ACL injury prevention education for youth and adolescent athletes. Design: Cross-sectional survey study design. Setting: Youth and adolescent student-athletes. Patients (or Participants): 387 student-athletes from throughout a large metropolitan region participated in this program. Matched pre/post-intervention survey data was collected from 258 participants (55.7% female; mean age=11.1 years; age range=7 to 17 years) Interventions (or assessment of risk factors): A team of highly-experienced sports medicine practitioners trained youth and adolescent athletes how to mitigate modifiable risk factors of ACL injury by performing sports-related movements (jumping/landing and acceleration/deceleration) with proper biomechanical technique. Additionally, participants learned how to identify and correct common sports-related movement deficiencies in themselves and others. Main outcome measurements: Outcome measures included knowledge, satisfaction, and self-management. Results: Overall mean knowledge scores increased by 115% (37.0 to 79.6, p< 0.001). 89.2% of participants reported that they could apply what they learned to reduce their risk of ACL injury while 76.7% of participants rated the program favourably. Conclusions: Community-based ACL injury prevention education programs can improve the knowledge and self-efficacy of a diverse group of young athletes. These findings support the inclusion of public health-based education interventions into comprehensive ACL injury prevention programs for young athletes to support program adoption and long-term behaviour change.